HUBUNGAN PENDIDIKAN, PARITAS, PEKERJAAN DAN LAMA MENOPAUASE DENGAN KUALITAS HIDUP PEREMPUAN MENOPAUSE DI PUSKESMAS KABANJAHE KABUPATEN KARO - Tarigan, Imarina; Br Sinuhaji, Lidya N; Sembiring, Mediana (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2019)
Menopause is a condition when physiological menstruation cycle concerning the human growing older. The increase in the number of growing old women will have its own problem with complaints about menopause. Although it does not cause death, it brings about uncomfortable condition and sometimes disturbs daily activities so that it can influence the life quality of menopause women. The research used analytic descriptive method with cross sectional design. It was conducted at Kabanjahe Puskesmas, Karo Regency, from February until June, 2018. The population was 103 menopause women who regularly visited Kabanjahe Puskesmas, taken by using purposive sampling technique. The result of univariate analysis showed that 71 respondents (68.9%) had good life quality. The result of bivariate analysis, using chi square test, showed that the factors which influenced life quality of menopause women were education (p=0.003), occupation (p=0.001), the duration of menopause (p= <0.001), but parity did not have any influence on the life quality of menopause women.The conclusion was that there was the correlation of education, occupation, duration of menopause, with the life quality of menopause women. It is recommended that menopause clinic and health care board which is related to health care providers be established.